THE MORPHOLOGY OF RADIAL GLIAL SPINAL CORD OF EMBRYOS AND HUMAN FETUSES - Shkolnikov, V.S.; Prykhodko, S.O.; Polishchuk, S.S.; Kryvoviaz, O.V.; Galunko, G.М. (World of Medicine and Biology, 2020)
The study of radial glia morphology and processes of targeted migration of neural stem cells in humans remains far from being resolved. The purpose of this study is to establish the morphological aspects of radial glia of spinal cord of human in prenatal period. Morphological examination of the spinal cord of human embryos and fetuses of 6-7 weeks up to 39-40 weeks was performed. Using anatomical, histological, immunohistochemical, and morphometric morphological aspects of the radial glia of the spinal cord were established. The results showed that strong expression of vimentin and CDX-2 radial glia fibers was observed up to 8-9 weeks. From 11-12 weeks, radial glia fibers retain a radial direction only in the middle part of the segments, which, in our view, is associated with the gradual involution of radial glia, which correlates with the formation of nuclear-neural complexes of gray matter. Until the moment of birth, vimentin-positive structures of radial glia gradually disappear and can be traced only in the neuroepithelium of segments.
Keywords: prenatal period; spinal cord; radial glia; neuroepitelium; immunohistochemical markers